Characterizations of Function Spaces via Boundedness of Commutators (Analysis in Theory and Applications, 2016)
In this paper, we give some creative characterizations of Campanato spaces via the boundedness of commutators associated with the Calderόn-Zygmund singular integral operator, fractional integrals and Hardy type operators. Furthermore, we put forward a few problems on the characterizations of Campanato type spaces via the boundedness of commutators.
Keywords: Campanato space; Morrey space; commutator.